DINAH’S STRUGGLE TO BE A WOMAN PREACHER IN GEORGE ELIOT’S ADAM BEDE: A FEMINIST APPROACH - PALUPI , IKA PRASETYANINGSIH (2007)
The object of this research is a novel entitled Adam Bede written by George Eliot publishing in 1859. This research focuses on Dinah’s struggle to be a woman preacher in George Eliot Adam Bede: feminist Approach. The objectives of this study are to analyze the novel based on it’s structural elements and on the feminist analysis. In analysing Adam Bede, the researcher uses qualitative method and feminist approach. In this study, the researcher uses two kinds of data sources namely primary and secondary data. The primary data source and the object of this study is the novel of Adam Bede, and the secondary data sources are the other references related to the analysis such as the author ’s biography, book of feminist issue, literary criticism and virtual ref erences especially about liberal feminism. The method of the data collection is literary research. The technique of data analysis is descriptive analysis. The outcome of the study shows the following conclusion. First, literary work may reflect the social reality when the novel was written. Second, George Eliot’s Adam Bede is interesting literary work which offers the complexes story to the reader. The theme of this novel is tells about the story of life that consists of love story, an affair, the tragic and decision of life. In the context of this novel, George Eliot creates the contrast between good and weak characters. Third, in the context of Adam Bede novel, George Eliot wants to illustrate the women’s condition in England at the periods of nineteenth century. The character of Dinah Morris tries to breaks the opinion about inequalities condition between men and women in religious duties from her position, role, participation, and rights. And finally, Dinah’s struggle to be a woman preacher is supported by the social condition of her society. She thinks that her society needs a religiou s practitioner to give an address about religious values. The character of Dinah Morris tries to prove that women have the abilities to handle the religious and social duties.